2014
DOI: 10.5603/mh.2014.0008
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of stress as a predictor of health consequences in Polish drilling platform workers. Longitudinal study: part I

Abstract: Stress adaptation (stress dynamics) and coping style included in the study in longer perspective show that those drilling platform workers, who declare the decrease of stress over the years, present worse health indicators than those, who declare variability in the ways of adaptation to stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Being satisfied with one's own health was found mostly (46%) to be at a good level (very satisfied). Leszczynska et al (2014) [35] noted that there was a strong significant correlation between the presence of health issues and dynamics of stress, and that there was a significant negative relationship between perceived level of health and again dynamics of stress. They also reported the perceived health median as 8 (between 0 and 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being satisfied with one's own health was found mostly (46%) to be at a good level (very satisfied). Leszczynska et al (2014) [35] noted that there was a strong significant correlation between the presence of health issues and dynamics of stress, and that there was a significant negative relationship between perceived level of health and again dynamics of stress. They also reported the perceived health median as 8 (between 0 and 10).…”
Section: Discussionmentioning
confidence: 99%
“…*Mann-Whitney U (z);**Kruskall-Wallis H (c 2 KW); ***Spearman's rho (r) the ages of 20 and 24, and PSY proved to be better in seafarers aged 20-24 and 25-34[35]. Another study on Lithuanian seafarers showed that while PHY, PSY, ENV and total QOL are the highest among seafarers aged 20-24, they are at the lowest among seafarers aged 55-64[27].…”
mentioning
confidence: 99%
“…In the discussions about work in an offshore environment, including drilling platforms, the concept of mental stress and the share and role of psychosocial factors as its sources should be given special attention ( Leszczyńska & Jeżewska, 2010 ; Leka, 2004 ). Exposure to detrimental physical and psychosocial factors takes place concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…The drilling rig employees are potentially exposed to the eruption of oil, gas, or fire, which puts them under the impact of permanent stress. They are also exposed to dangers related to offshore drilling operations, ‘access’ to the workplace by helicopter or, in the case of adverse weather conditions, by ship ( Leszczyńska & Jeżewska, 2010 ; Leszczyńska, 2016 ; Wang & Chen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stress is also a risk factor for astronauts undergoing long duration space travel that has physiological and psychological implications [22]. Not only do daily stressors lead to irritability, short temperedness, and a lack of concentration, but psychological stress can have long-term effects on an individual's sympathetic nervous system [7,9].…”
Section: Physical and Psychological Effects Of Stressmentioning
confidence: 99%